Study of the Germination of Six Begonia Species as an Effort to Preserve Genetic Resources - Semarayani, Cokorda Istri Meyga; Rahayu, Ayyu (Biosaintifika: Journal of Biology & Biology Education, 2021)
Begonia is an ornamental plant that has a high level of morphological diversity. Begonia propagation is mostly done vegetatively and very rarely to propagate sexually. Therefore, this study was conducted to determine the ability of six types of Begonia seeds to germinate. Six types of Begonia, namely B. x albopicta W. Bull 'Coral Rubra', B. gambutensis Ardi & D.C.Thomas, B. multistaminea Burt-Utley, B. nelumbifolia Schltdl. & Cham., B. ulmifolia Wild. and B. varipeltata D.C.Thomas. were grown in a petri dish and placed in a growth chamber with a temperature of 23.6 ℃, humidity of 74.5%, and a light intensity of 3,431 lux. The results showed that the different types of Begonia showed significant differences in all the parameters tested. B. nelumbifolia required 7.89 ± 0.18 days to germinate and is the fastest time than other types. The highest percentage of seed germination was also obtained by this species, amounting to 63.22%. In addition, B. nelumbifolia showed the best response to the germination rate coefficient, germination rate index, and germination index. This study revealed complete information about the germination of six types of Begonia. In addition, the ability to produced many seeds and the ease of germination made this plant have the potential to be cultivated through seeds. Furthermore, the information can be used as a basis for seed storage as an ex-situ conservation method to maintain genetic diversity.